Black Musician and the White City Race and Music in Chicago, 1900-1967 - Absher, Amy (University of Michigan Press, 2014)
Amy Absher's The Black Musician and the White City tells the story of African American musicians in Chicago during the mid-twentieth century. While depicting the segregated city before World War II, Absher traces the migration of black musicians, both men and women and both classical and vernacular performers, from the American South to Chicago during the 1930s to 1950s.Absher takes the history beyond the study of jazz and blues by examining the significant role that classically trained black musicians played in building the Chicago South Side community. By acknowledging the presence and importance of classical musicians, Absher argues that black migrants in Chicago had diverse education and economic backgrounds but found common cause in the city's music community.